2008
DOI: 10.1002/jctb.2054
|View full text |Cite
|
Sign up to set email alerts
|

Combined permeable pavement and ground source heat pump systems to treat urban runoff

Abstract: BACKGROUND: This paper assesses the functioning of the next generation of permeable pavement systems. The overall concept is to combine traditional permeable pavement systems with ground source heat pump systems. Long-term research to provide data concerning nutrient reductions and microbial activity within experimental pavement rigs is required.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
15
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 29 publications
4
15
0
Order By: Relevance
“…A typical composition of layers comprises a lower sub-base (250 mm), an upper sub-base (100 mm), a geotextile, a clean 5-mm stone layer (50 mm) and finally paving blocks (80 mm) at the top (Figures 1-3). The porous Inbitex geotextile made of polyethylene and polypropylene fibres was placed in the top part of the upper base, as this is the area where considerable microbial degradation of pollutants is likely to take place [13]. Either Inbitex on its own or Inbitex together with an impermeable layer (Terram Drainage Composite, Terram Geosynthetics, Gwent, UK), called composite, and were used in the experimental bins.…”
Section: Figurementioning
confidence: 99%
“…A typical composition of layers comprises a lower sub-base (250 mm), an upper sub-base (100 mm), a geotextile, a clean 5-mm stone layer (50 mm) and finally paving blocks (80 mm) at the top (Figures 1-3). The porous Inbitex geotextile made of polyethylene and polypropylene fibres was placed in the top part of the upper base, as this is the area where considerable microbial degradation of pollutants is likely to take place [13]. Either Inbitex on its own or Inbitex together with an impermeable layer (Terram Drainage Composite, Terram Geosynthetics, Gwent, UK), called composite, and were used in the experimental bins.…”
Section: Figurementioning
confidence: 99%
“…This section is concerned with the critical review of a long-term and well-reported research study [3,10,22] undertaken by the The University of Edinburgh for Hanson Formpave (Hanson UK, 14 Castle Hill, Maidenhead SL6 4JJ, England, UK). Several types of combined permeable pavement and ground source heating pump systems used to treat urban runoff were evaluated.…”
Section: Essential Backgroundmentioning
confidence: 99%
“…The highest concentrations were recorded close to the first two (i.e., the shallowest) sampling points for each bin. This indicates that the most intensive microbial activity takes place around the geotextile [28,29], which was responsible for lower microbial counts within the outflow of most systems during the majority of the monitoring period [3].…”
Section: Review Of Key Findingsmentioning
confidence: 99%
See 1 more Smart Citation
“…In this context Sustainable Urban Drainage Systems (SUDS) as Pervious Pavements Systems (PPS) have important advantages , not only in the reduction of runoff by decreasing impermeable areas (Rushton, 2001), but also in the reduction of pollutants (Coupe et al, 2003), recharge of aquifers (Ferguson, 2011), erosion control (Wright, 2008) and increased urban amenity (Ellis et al, 2004). The main applications of PPS in urban areas are car parks for light traffic where PPS have the potential to occupy large urban areas (Shu et al, 2011), access roads for residential streets, parking areas and roads for recreational facilities such as golf courses and bike lanes, amongst others (Scholz and Grabowiecki, 2009). …”
Section: Introductionmentioning
confidence: 99%